Numerical Analysis of Unsteady Internal Flow Characteristics of Impeller-Guide Vane in a Vertical Axial Flow Pump Device - Yang, Fan; Chang, Pengcheng; Jian, Hongfu; Lv, Yuting; Tang, Fangping; Jin, Yan (Frontiers in Energy Research, 2022)
A vertical axial flow pump device has the characteristics of low head and large flow and has various forms, simple structure, and flexible installation. It is widely used in low-head pumping stations in plain areas. In order to explore the transient characteristics of the internal flow in the impeller and guide vane of the vertical axial flow pump at different flow rates, this article analyzes the internal flow field distribution on the surface of the impeller blade, the velocity and pressure distribution of the impeller inlet and outlet, and the pressure pulsation characteristics of the impeller. The flow field characteristics of the guide vane section, the entropy production loss, and the main frequency change of the pressure pulsation inside the guide vane are analyzed at different radii. The results show that under 0.8 Qbep condition, the streamline distortion area of the blade working face accounts for the largest part of the blade area, and the streamline distortion area of the blade surface decreases significantly at 1.2 Qbep. The circumferential pressure distribution at the impeller inlet presents four high-pressure regions and four low-pressure regions, and the number of regions is consistent with the number of impeller blades. The ratio of axial force to flow rate of 0.8Qbep, 1.0Qbep, and 1.2Qbep is approximately 11:10:9. The radial force on the impeller is the largest under the condition of 0.8 Qbep, and the radial force on the impeller is not significantly different between 1.0 Qbep and 1.2 Qbep. The pressure pulsation amplitude gradually decreases from the inlet to the outlet of the guide vane.